Strategi Korea Selatan dalam Pemulihan Krisis Moneter Tahun 1997 Melalui IMF - Kaloka, Yola Natasyah; Tegar, Putri; Eldy, M (Nation State: Journal of International Studies, 2019)
During the monetary crisis in 1997, South Korea's economic growth increased the recession. This is due to a large amount of foreign money made by the maturing Chaebol. Add to that by reducing South Korea's very significant export revenue paid to the country's foreign exchange reserves. In line with this, it could lead to distrust of foreign creditors, so they withdrew funds that had planted in large-scale investment agreements several years earlier. Over time, South Korea could no longer run economic turmoil. How to improve the Government to collaborate with the IMF on November 21, 1997, as an effort to stabilize national finance, with total funding of US $ 57 billion. In accordance with the role of the IMF, it means that South Korea has approved the procedures provided by the IMF that participated in the intervention of its national political economy. This paper will explained how the role of the IMF as an institutional liberal institution in South Korea, what forms of intervention carried out by the IMF, and how South Korea has utilized IMF assistance in its national economic recovery strategy.